It’s Time to Examine the Impact of Genetic Susceptibility on the Incidence of Diabetes among HIV-Infected Individuals - Kyle J. Gaulton; Glen N. Gaulton (HIV/AIDS Research and Treatment-Open Journal, 2016)
The remarkable advances in application of anti-retroviral therapy (ART) to treat HIV infection has had a profound impact on the HIV epidemic as well as improved the quality and longevity of life for those who receive such treatment. Nonetheless, as individuals receiving ART live longer, they may develop chronic non-communicable disease at an increased incidence and/or severity when compared to non infected and/or untreated individuals. Prime examples of this include cardiovascular and neurological disease, as well as metabolic syndrome and diabetes mellitus.